Management of Barrett’s Esophagus - Ziad Younes; Mark D Duncan; John W Harmon (Canadian Journal of Gastroenterology)
There have been major recent advances in the understanding of the pathogenesis and epidemiology of Barrett’s esophagus and adenocarcinoma of the esophagus. The advent of potent acid suppression with proton pump inhibitors and safe, minimally invasive antireflux procedures has made alleviating symptoms and eliminating peptic complications achievable goals for the vast majority of patients. Endoscopic surveillance of Barrett’s esophagus is considered the standard of care and is widely used in clinical practice. Neither medical nor surgical antireflux procedures, however, result in the regression of Barrett’s esophagus in any consistent manner. Thermal and chemical endoscopic ablation techniques show promise in both the management of high grade dysplasia and the reversal of Barrett’s esophagus, but these techniques are still of unproven benefit, and can be costly and risky. Therefore, prospective and controlled studies with long term follow-up are needed before incorporating ablative techniques into routine clinical practice. Management of high grade dysplasia remains controversial. Alternative management strategies include surveillance, resection or ablation, tailored to the individual patient and the available expertise. Targets for future research include defining appropriate surveillance intervals; finding biological markers that identify patients at higher risk of progressing to cancer; defining the cancer risk and the appropriate management of patients with short segment Barrett’s esophagus; understanding the natural history of dysplasia and comparing alternatives for the management of high grade dysplasia; and studying whether surgical management can delay or prevent the progression to dysplasia and adenocarcinoma.